Higher plasma leptin levels are associated with reduced left ventricular mass and left ventricular diastolic stiffness in black women: insights from the Genetic Epidemiology Network of Arteriopathy (GENOA) study. Issue 8 (August 2018) - Kamimura, Daisuke; Suzuki, Takeki; Wang, Wanmei; deShazo, Matthew; Hall, John; Winniford, Michael; Kullo, Iftikhar; Mosley, Thomas; Butler, Kenneth; Hall, Michael
Abstract Our previous experimental animal data suggest a beneficial effect of leptin on LV structure and function. We hypothesized that leptin levels are associated with lower LV mass and myocardial stiffness which are important risk factors for the development of heart failure with preserved ejection fraction (HFpEF). We evaluated 1172 blacks, in which the prevalence of HFpEF is quite high, with preserved LV ejection fraction (EF > 50%) from the Genetic Epidemiology Network of Arteriopathy Study (mean age 62.9 years, 72% women), a community-based study to identify genes influencing blood pressure and target organ damage due to hypertension. Associations between leptin levels and indices of LV structure and function were evaluated using generalized estimating equations accounting for clustering in siblings. LV myocardial stiffness was evaluated using diastolic wall strain (DWS) measured by echocardiography. Analyses were stratified by sex because leptin levels were three times higher in women than men (p  < 0.001). After adjustment for confounders, higher leptin levels were associated with lower LV mass (coefficient for 1 s.d. increase of leptin level: −5.825 g, 95% CI: −9.755 to −1.895 g, P  = 0.004) and higher DWS (lower LV stiffness) (coefficient for 1 s.d. increase of leptin level: 0.009, 95% CI: 0.002–0.015, P  = 0.007) in women. There were no statistically significant associations in men. In women, there were interactions between leptin levels and body mass index quartiles on LV mass and stiffness (p  < 0.05 for both). Higher leptin levels were associated with lower LV mass and stiffness in obese but not lean black women.